1973
DOI: 10.4141/cjas73-020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Level of Copper Supplement and Removal of Supplemental Copper From the Diet on the Performance of Growing-Finishing Pigs and Accumulation of Copper in the Liver

Abstract: ELr-Ior, J. I. lxo AvEn, M. A. 1973

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
2

Year Published

1974
1974
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
5
1
2
Order By: Relevance
“…The station x treatment interaction indicated these differences affected the response due to dietary copper. However, the inconsistency among the stations observed in this study was not unexpected in that recent reports by a number of authors, among them Barber et al (1968), Beames (1969), Kline et al (1972) and Hedges and Komegay (1973) have indicated responses to 250 ppm of supplementary copper, while others have shown no beneficial response to this level of copper (Livings.tone and Livingston, 1968;Parris and McDonald, 1969;Elliot and Bowland, 1970;Amer and Elliot, 1973).…”
Section: Remits and Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The station x treatment interaction indicated these differences affected the response due to dietary copper. However, the inconsistency among the stations observed in this study was not unexpected in that recent reports by a number of authors, among them Barber et al (1968), Beames (1969), Kline et al (1972) and Hedges and Komegay (1973) have indicated responses to 250 ppm of supplementary copper, while others have shown no beneficial response to this level of copper (Livings.tone and Livingston, 1968;Parris and McDonald, 1969;Elliot and Bowland, 1970;Amer and Elliot, 1973).…”
Section: Remits and Discussioncontrasting
confidence: 58%
“…However, some reports have been contradictory in regard to effects of copper on performance of pigs. Livingstone and Livingston (1968), Parris and McDonald (t969), Elliot and Bowland (1970) and Amer and Elliot (1973) reported no beneficial growth response to 200 or 250 ppm of supplemental copper, while others (Barber et al, 1968;Beames, 1969;Kline, Hays and Cromwell, 1972) have obtained growth responses with 250 ppm. Miller (1969) and Gipp, Pond and Walker (1973b) reported improved growth rates from feeding copper during the growing phase but not during the finishing period.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Assim, um dos modos de ação dos agentes antimicrobianos, como promotores do crescimento, pode ser pela redução deste quadro. Apesar de muitas teorias sobre o modo de ação do cobre terem sido sugeridas, há evidências de que elevados níveis dietéticos deste micromineral atuam sobre os microrganismos do trato gastrintestinal de aves e suínos (Bunch et al, 1961;Elliot & Amer, 1973;Menten, 1995). Os resultados obtidos nesta pesquisa podem estar relacionados com este mecanismo de ação, uma vez que o vazio sanitário de cerca de 90 dias, a qualidade das instalações, bem como as práticas de desinfecção adotadas podem ter proporcionado um ambiente com baixa concentração de microrganismos patogênicos.…”
Section: Resultsunclassified
“…A ação antimicrobiana ou modificador da flora microbiana do trato gastrintestinal é descrita e discutida em inúmeros trabalhos científicos (Bunch et al, 1961;Elliot & Amer, 1973;Menten, 1995). Além disso, alguns trabalhos (Zhou et al, 1994 a, b;Apgar et al, 1995) têm sugerido que o Cu pode Ter uma ação metabólica ou sistêmica na promoção do crescimento de leitões recém-desmamados.…”
Section: Introductionunclassified